The predictive value of perirenal fat thickness in systemic inflammatory response syndrome after percutaneous nephrolithotomy - Jue Gong; Wei Ouyang; Wen Liu; Guangming Yin; Peng Yuan (Annals of Medicine)
Objective It was hypothesized that perirenal fat (PRF) might be associated with systemic inflammatory response syndrome (SIRS) after percutaneous nephrolithotomy (PCNL). The aim of this study was to investigate risk factors, including perirenal fat thickness (PRFT), that may contribute to SIRS after PCNL.Methods 169 patients with unilateral renal stones who underwent PCNL at our institution between January 2020 and December 2023 were retrospectively included. Based on the occurrence of SIRS after PCNL, patients were divided into non-SIRS group (n = 136) and SIRS group (n = 33). Independent risk factors for the development of SIRS after PCNL were identified by using univariable and multivariable logistic regression analyses.Results It was found that PRFT at the surgical side was significantly higher in patients with SIRS than those without SIRS (median 4.8 cm vs. 5.2 cm, p = 0.029). The results of univariate logistic regression analysis showed that high PRFT (p = 0.005), diabetes (p = 0.016), high serum procalcitonin (p = 0.004), and positive urine culture (p = 0.008) were associated with SIRS after PCNL. The results of multivariable logistic regression analysis revealed that high PRFT (OR 1.263, 95% CI 1.046–1.524; p = 0.027), diabetes (OR 4.012, 95% CI 1.494–10.773; p = 0.035), high serum procalcitonin (OR 1.367, 95% CI 1.095–2.086; p = 0.006), and positive urine culture (OR 3.574, 95% CI 1.092–11.700; p = 0.015) might be independent predictors for SIRS after PCNL.Conclusion Patients with high PRFT, diabetes, high serum procalcitonin, and positive urine culture may be at a higher risk of SIRS after PCNL. Preoperative comprehensive evaluation and postoperative close monitor should be considered on these patients.